Study of Nuclear Properties of High Purity Germanium - Abbood, Noor Mohammed; Ebrahiem, Sameera Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In the current study, the observations depended on some nuclear properties of Germanium isotopes that are used for multiple purposes by studying transverse sections when interacting with charged particles such as alpha and proton particles and their interaction with gamma rays of conjugal isotopes relative to the stability of the nucleus with other nuclei. By calculating the cross sections of the  (Î±, )   ,  (Î³,x)0-NN-1, (Î³,2n)  , (Î±,p)  reactions of  isotope. Nuclear reactions in the newer global libraries (EXFOR, ENDF, JEF, JEFF, GENDL) have been published to identify appropriate energies in calculating the inverse nuclear reactions of the ground State.